Rain water infiltration assesment using the Guelp permeameter - García Rodríguez, Manuel (M+A. Revista Electrónica de Medioambiente, 2013)
This paper presents a study on infiltration capacity of the soil in a rural land in order to know its behavior against possible flooding during periods of heavy rainfall. The determination of the runoff coefficient, the water balance soil on different assumptions and permeability testing with the Guelph permeameter have provided information on soil behavior as retaining element of rainwater with extraordinary rainfall.
Keywords: Guelph permeameter; hydrogeology of Mesa de Ocaña; infiltration assessment.